YUK LES: INFORMATION SYSTEMS ON ONLINE PRIVATE COURSE SERVICES BASED ON MOBILE APPLICATION - Lydia Liliana; Adam Surya Wijaya; Nico Fernando; Henny Hartono; Dwi Hosanna Bangkalang (Universitas Bunda Mulia, 2019)
One way to improve students' academic and non-academic abilities is by taking tutoring. Tutoring is an effort to achieve maximum learning outcomes in accordance with the field of interest. In the era of technological revolution 4.0, we are always demanded to be up to date on their abilities in non-academic / soft skills such as video editing, programming, dance, music, multimedia, etc. Education 4.0 should be able to provide easy access to education and mobility in learning formal and non-formal fields. The application